The legal basis for community service as an alternative punishment in Malaysia - Tg Zainudin, Tg Noor Azira; Abdul Rahim, Anita; Samuri, Mohd. al-Adib; Abdul Rahim, Adibah (Medwell Publishing, 2014)
Community service order is now slowly gaining attention from various authorities in the Malaysian legal circle. The question that comes to mind amidst the development in this non-custodial punishment is whether there is existing legal basis for the application of the community service order. It is crucial to identify, the legal foundation that can support community service order in Malaysia to avoid issues of illegibility of orders imposed. This study aims to highlight the legal provisions that are in existence in the Malaysian jurisdiction relating to community service order and the extent of its applicability.